GAMBARAN TENTANG PENGETAHUAN GIZI DAN STATUS GIZI PADA ANAK USIA SEKOLAH DASAR DI SDN 34 PONTIANAK KOTA - Cyndy Febrianty Dei; Didik Hariyadi; Jurianto Gambir (Media Gizi Khatulistiwa, 2026)
Background: Nutrition intake in school children is very important to note because school children are susceptible to nutritional problems.Based on RISK data in 2018, nutrition problems in school kids aged 5-12 years are 9.3% lean, divided into 2.5% very thin and 6.8% thin.Nutrition problems are more prevalent with 20.6% obesity 11.1% and very fat (obesity) 9.5%.The prevalence of short incidents is 23.6% with 6.7% very short and 16.9% very short.Background: The intake of nutritional substances in school girls is important to observe because school kids are vulnerable to nutrient problems.Based on RISKS data in 2018 the nutrition problem of school children aged five-12 years according to the age mass index is 9.3% thin, which is divided by 2.5% very thick and 6.8%.The nutritional problem with more prevalence is 20.6% fat, 11.1% very fat, 9,5% very fat and 16.6% very short incidence. Objective: The aim of this study is to find out a picture of nutritional knowledge and nutritional status in children of primary school age in SDN 34 Pontianak City. Research method: This type of research is descriptive research which is structured using the random sampling method, namely simple random sampling, for example a member of the population named A is given the number 2, then when the number 2 is drawn, the member of the population named A is selected to be the sample where the number of samples that will be used as many as 58. The data analysis used is univariate, namely frequency distribution. Results: Based on the results of research conducted at SDN 34 Pontianak City, the highest percentage of elementary school children's knowledge level was obtained, namely 53.4%. with the good category and the lowest percent result, namely 17.2% in the poor category. Meanwhile for nutritional status with the BMI/U index The highest percent result was 62.1% in the normal nutrition category and the lowest percent result was 3.4% in the obesity category. Conclusion: Based on the research that has been carried out, it can be seen that the knowledge of class 5 children at SDN 34 Pontianak City is said to be good in terms of knowledge level and for the nutritional status of class 5 at SDN 34 Pontianak City, most of them have normal nutritional status.